2011
DOI: 10.1186/1475-2891-10-32
|View full text |Cite
|
Sign up to set email alerts
|

Changes in total body bone mineral density following a common bone health plan with two versions of a unique bone health supplement: a comparative effectiveness research study

Abstract: BackgroundThe US Surgeon General's Report on Bone Health suggests America's bone-health is in jeopardy and issued a "call to action" to develop bone-health plans that: (1) improve nutrition, (2) increase health literacy and, (3) increase physical activity. This study is a response to this call to action.MethodsAfter signing an informed consent, 158 adults agreed to follow an open-label bone-health plan for six months after taking a DXA test of bone density, a 43-chemistry blood test panel and a quality of life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In a double-blind cross-over trial, a preparation of calcium from oyster shell and heated seaweed extract (Cystophyllum fusiforme), providing 900-mg Ca per day, was shown to increase lumbar spine bone density of 58-year-old postmenopausal women after 6 and 24 months of supplementation, when compared to placebo. A later study run with another plant sourced form of calcium made by milling whole, live-harvested sea algae found on the South American coastline and provided within a general bone health plan including physical activity and other general dietary recommendations led to increased bone mineral density in adults aged 18-85 (Michalek et al, 2011). It was hypothesized that this form of calcium was better absorbed than calcium from other sources, since parathyroid hormone was decreased to a greater extent with this preparation than with milk in a cross-over trial run in eight young 18-19-year-old female volunteers (Ohgitani et al, 1997).…”
Section: Seaweeds and Osteoporosis: Clinical Studiesmentioning
confidence: 99%
“…In a double-blind cross-over trial, a preparation of calcium from oyster shell and heated seaweed extract (Cystophyllum fusiforme), providing 900-mg Ca per day, was shown to increase lumbar spine bone density of 58-year-old postmenopausal women after 6 and 24 months of supplementation, when compared to placebo. A later study run with another plant sourced form of calcium made by milling whole, live-harvested sea algae found on the South American coastline and provided within a general bone health plan including physical activity and other general dietary recommendations led to increased bone mineral density in adults aged 18-85 (Michalek et al, 2011). It was hypothesized that this form of calcium was better absorbed than calcium from other sources, since parathyroid hormone was decreased to a greater extent with this preparation than with milk in a cross-over trial run in eight young 18-19-year-old female volunteers (Ohgitani et al, 1997).…”
Section: Seaweeds and Osteoporosis: Clinical Studiesmentioning
confidence: 99%
“…This clinical investigation approach can be considered as lying within the conceptual scope of “Comparative Effectiveness Research (CER)” ( 12 ). So far, few studies have applied a CER design in the field of clinical nutrition, such as that comparing the effects of two plant-source forms of calcium supplements on bone mineral density ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although CER will pose challenges for medical and nutritional industries, it will present numerous opportunities to improve the information base supporting nutritional products, especially when they are integrated into other medical interventions ( 166 ) . Recent CER nutrition studies have been reported on the bone effects of several vitamin D and Ca supplement regimens ( 167 , 168 ) .…”
Section: Study Designs To Test the Effects Of Food Products On Bone Mmentioning
confidence: 99%